Pirolisis Kayu Pinus (Pine Merkusil) Menjadi Bio - Oil Menggunakan Katalis NiMo/NZA - Irwan Irwan; Syaiful Bahri; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Availability of petroleum as a fuel that can not be updated further reduced by increasing the use of oil for human needs. For that we need to do a conversion innovation of energy that do not depend on fossil resources and can be renewable and have an output similar to that produced from fossil resources. One such innovation is the conversion of biomass derived from pine merkusii wood to bio-oil. Bio-oil can be produced by pyrolysis of pine merkusii wood with catalyst NiMo/NZA. Objective this research to produce bio-oil from pine merkusii wood as an alternative fuel, studying the effect of the weight ratio of the catalyst NiMo/NZA to the biomass, studying the effect of metal impregnation Nickel (Ni) and Molybdenum (Mo) on Natural Zeolite deAluminated (NZA) and characterization of physical properties and chemical properties of bio-oil. Process pyrolysis was carried out at 320 0C, silinap 500 ml, 50 grams of biomass with + 100-200 mesh sieve size, variations in the catalyst NiMo/NZA to the biomass of 3%; 5% and 7% by weight and Nickel-Molybdenum metal variation on NZA of 0%; 1%; 2% and 3%. The results of this study produce bio-oil yields the largest on the use of the catalyst NiMo/NZA 5% by weight of the metal content of 3% by 65,076%. Characterization of physical properties of bio-oil obtained in the form of density 0,986 g/ml, 15,816 cSt viscosity, acidity 36,879 mg NaOH/g sample, flash point 48 0C and calorific value 39,12 MJ/kg. While the characterization of the chemical properties of bio-oil using Gas Chromatography-Mass Spectroscopy (GCMS) obtained some dominant chemical components such as phenol (19,42%), toluene (13,48%), tetradecanoic acid (12,93%), phenol,2-methoxy (12,18%), acetone (11,72%), benzene,1,2-dimethoxy (9,30%), and 2-furancarboxaldehyde (3,76%).Keywords: bio-oil, catalyst NiMo/NZA, pine merkusii wood, pyrolysis